Influence of solvents on the growth of zinc oxide nanoparticles fabricated by microwave irradiation - Canh, Ta Dinh; Tuyen, Nguyen Viet; Long, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics, 2009)
Abstract